Common sense and medical sciences: a sociological study - Tandi, Subal; Harpal, Utkal (Journal of Social Review and Development, 2026)
The relationship between common sense and medical sciences represents a critical yet often overlooked area of sociological inquiry. Common sense, shaped by everyday experiences, cultural beliefs, traditions, and social norms, plays a significant role in how individuals perceive health, illness, diagnosis, and treatment. Medical sciences, on the other hand, are grounded in scientific rationality, standardized knowledge, and evidence-based practices. This sociological study examines the interaction, tension, and coexistence between common sense knowledge and biomedical understanding in healthcare settings. It explores how patients’ lay interpretations of symptoms, illness causation, and healing practices influence health-seeking behavior, treatment compliance, and doctor–patient relationships. The study also analyzes how medical professionals respond to, negotiate with, or dismiss common-sense explanations during clinical encounters. Drawing on sociological theories of knowledge, particularly the distinction between lay knowledge and expert systems, the study highlights how power, authority, and social context shape medical decision-making. It argues that common sense is not merely irrational or unscientific but socially constructed and culturally meaningful. In pluralistic societies like India, common sense often intersects with traditional medicine, religious beliefs, and indigenous healing practices, creating both complementarities and conflicts with modern medical science. The abstract emphasizes the need for culturally sensitive healthcare that recognizes patients’ lived experiences while maintaining scientific rigor. By bridging common sense and medical science, the study contributes to a more inclusive, humane, and socially responsive healthcare system.